Smart Kitchen Safe (K-safe product) / Siti Rofilah Ismail, Noor Atika Ab Wahab and Noor Ammirrah Md Uzir - Ismail, Siti Rofilah; Ab Wahab, Noor Atika; Md Uzir, Noor Ammirrah
After prefix observation towards the family and student life, the team had chosen a product that can be solve part of problem happen with them. The product is Smart Kitchen Safe. This product time-lock container for diverse of things such as food, gadgets and other item to lock. Its also support by material that have temperature which is change food or drink to be hot and cold. This product is suitable to family have at home and also for student to keep their important things.